A Numerical Simulation Study of the Impact of Kesterites Hole Transport Materials in Quantum Dot-Sensitized Solar Cells Using SCAPS-1D - Sindisiwe Jakalase; Azile Nqombolo; Edson L. Meyer; Mojeed A. Agoro; Nicholas Rono (Nanomaterials)
Energy generation and storage are critical challenges for developing economies due to rising populations and limited access to clean energy resources. Fossil fuels, commonly used for energy production, are costly and contribute to environmental pollution through greenhouse gas emissions. Quantum dot-sensitized solar cells (QDSSCs) offer a promising alternative due to their stability, low cost, and high-power conversion efficiency (PCE) compared to other third-generation solar cells. Kesterite materials, known for their excellent optoelectronic properties and chemical stability, have gained attention for their potential as hole transport layer (HTL) materials in solar cells. In this study, the SCAPS-1D numerical simulator was used to analyze a solar cell with the configuration FTO/TiO2/MoS2/HTL/Ag. The electron transport layer (ETL) used was titanium dioxide (TiO2), while Cu2FeSnS4 (CFTS), Cu2ZnSnS4 (CZTSe), Cu2NiSnS4 (CNTS), and Cu2ZnSnSe4 (CZTSSe) kesterite materials were evaluated as HTLs. MoS2 quantum dot served as the absorber, with FTO as the anode and silver as the back metal contact. The CFTS material outperformed the others, yielding a PCE of 25.86%, a fill factor (FF) of 38.79%, a short-circuit current density (JSC) of 34.52 mA cm−2, and an open-circuit voltage (VOC) of 1.93 V. This study contributes to the advancement of high-performance QDSSCs.